Rival Visions How Jefferson and His Contemporaries Defined the Early American Republic. - Gish, Dustin (Jeffersonian America., 2021)
"The emergence of America as a new nation on the world stage conjured rival visions of the early American Republic in the mind's eyes of both leading statesmen at home and attentive observers abroad. Jefferson envisioned the newly independent states as a loose federation of autonomous republics united by common experience, mutual interest, and an adherence to principles of natural rights. His views on popular government and the American experiment in republicanism, and later the expansion of its empire of liberty, helped fashion an influential account of the new nation, but also served as a touchstone for other, competing perspectives. While persuasive in some respects, his vision of early America did not stand alone as an uncontested paradigm. Among his contemporaries, Franklin, Washington, Adams, Hamilton, and Madison articulated their visions for the early American Republic, along with and often over against that of Jefferson, each vying to shape the new nation. Even beyond America, in this age of successive revolutions and crises, foreign statesmen began to formulate their own accounts of the new nation. This volume studies how these vigorous debates and competing rival visions forged the early American Republic in the formative epoch after the revolution, and what we learn about Jeffersonian America as it emerged from this crucible of intense rivalry"--